(untitled) - Bradley, Sean V. (Hoboken, New Jersey, 2015)
Rank higher in search results with this guide to SEO and content building supremacy. Google is not only the number one search engine in the world, it is also the number one website in the world. Only 5 percent of site visitors search past the first page of Google, so if you're not in those top ten results, you are essentially invisible. Winning the Game of Googleopoly is the ultimate roadmap to Page One Domination. The POD strategy is what gets you on that super-critical first page of Google results by increasing your page views. You'll learn how to shape your online presence for Search Engine Optimization, effectively speaking Google's language to become one of the top results returned for relevant queries. This invaluable resource provides a plan that is universal to any business in any industry, and provides expert guidance on tailoring the strategy to best suit your organization. Coverage includes an explanation of the mechanics of a search, and how to tie your website, paid ads, online reputation, social media, content, images, and video into a winning SEO strategy that pushes you to the front of the line. The Page One Domination strategy incorporates all the ways in which you can beef up your Internet presence and online reputation. This book is a clear, straightforward guide that will knock down the silos of the Internet and teach you exactly how to integrate all aspects of content creation into a synergistic, SEO strategy.
Keywords: Tìm kiếm tài nguyên thông tin điện tử,Electronic information resource searching